Protective effect of wuzibushen recipe on follicular development via regulating androgen receptor in polycystic ovary syndrome model rats - Lanyawen Hu; Yan Liu; Panpan Dong; Ping Ye (Taylor & Francis Group, 2023)
Objectives The study aimed to explore the role and mechanism of WZBS recipe on PCOS.Methods PCOS model was established. After modeling, PCOS rats were intragastrically administered with Diane-35 or WZBS recipe (6.93 g/kg/d). Then, the ovarian and uterine morphology were observed, the estrous cycle was assessed. HE and oil red O staining were conducted for ovarian morphological analysis and counting ovarian follicle and corpora lutea number. Furthermore, the serum content of testosterone (T) and sex-hormone-binding globulin (SHBG) were assessed by ELISA kits. The androgen receptor (AR), CX43 mRNA and protein expression were measured by q-PCR and Western blot.Results WZBS recipe increased uterine implanted blastocysts, reduced cystic dilated follicles, and normalized estrous cycle in PCOS rats. Meanwhile, WZBS recipe alleviated ovarian injury, increased mature follicles and corpora lutea number in PCOS rats. Moreover, WZBS recipe decreased serum T content, AR expression and increased serum SHBG content, CX43 expression in PCOS rats.Conclusions This study reveals that WZBS recipe may attenuate PCOS by protecting follicular development via down-regulating AR.